2020
DOI: 10.15294/active.v9i2.39056
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Volleyball Basic Technique Through Games Approach

Abstract: The study aimed to develop volleyball basic technique using games approach. The game help students to create a sport is more interesting. A study used to research and development using Borg and Gall method. There are ten steps in research. Process of collecting data used observation, interview, test, and questionnaire. Data analysis used peer assessment and judgment expert. The study conducted in Junior High School Palembang. The results of the findings show that the basic technique of volleyball consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Other research results by [2], [3], [5] stated that agility has a direct effect on over-passing skills. This confirms that agility has a direct effect on volleyball passing skills.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Other research results by [2], [3], [5] stated that agility has a direct effect on over-passing skills. This confirms that agility has a direct effect on volleyball passing skills.…”
Section: Discussionmentioning
confidence: 88%
“…Volleyball requires agility, coordination and reaction ability for playing and a good suspicion to lift and hit the ball. In volleyball, changes in the speed of game and scoring system the set finishes quickly, so players need a high level of agility, coordination and reaction ability [1], [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e study found that the main defensive formations in various countries are the back row defence with free men as the core [15]. Compared with foreign countries, the women's volleyball team has a stable performance in the game and a high pilling rate.…”
Section: Related Workmentioning
confidence: 97%
“…From the results of previous research, there are many training methods that can improve volleyball smash skills. Variations of basic volleyball technique exercises to improve the volleyball skills of junior high school students [10]. Relationship between general jump types and spike jump performance in elite female and male volleyball players [11].…”
Section: Discousionmentioning
confidence: 99%